Dry Socket in Smokers after Odontectomy - Christian F. Poluan; Pritartha S. Anindita; Christy N. Mintjelungan (Universitas Sam Ratulangi, 2022)
Abstract: Dry socket is delayed healing of a socket resulted from extraction due to the release of blood clot leaving visible bone surface. There are several risk factors of dry socket such as dentistry skills, perioperative infection, gender, extraction site, use of oral contraceptives, smoking, use of local anesthetics with vasoconstrictors, and position of impacted third molars. The risk of dry socket in smokers is greater than in non-smokers. This study aimed to obtain the occurrence of dry socket in smokers after odontectomy. This was a literature review study using databases of Google Scholar, PubMed, and Clinical Key. The results obtained 10 articles that were relevant to the topic of discussion. The incidence of dry socket was higher in smokers than in non-smokers. The high incidence of dry socket in smokers was influenced by the ingredients contained in cigarettes, among others, nicotine, carbon monoxide, and hydrogen cyanide. Nicotine affected the rate of epithelialization and blood flow, carbon monoxide caused a decrease in oxygen levels, and hydrogen cyanide could damage the metabolism of cellular respiration. These were related to the phase of wound healing at the stage of inflammation and epithelialization of fibroplasia. In conclusion, the incidence of dry socket after odontectomy is more common in smokers than in non-smokers.Keywords: dry socket; smoking; odontectomyÂ Abstrak: Dry socket merupakan keadaan penyembuhan soket bekas pencabutan yang tertunda karena lepasnya bekuan darah sehingga permukaan tulang terlihat. Terdapat beberapa faktor risiko terjadinya dry socket seperti keterampilan dokter gigi, infeksi perioperatif, jenis kelamin, lokasi pen-cabutan, penggunaan oral kontrasepsi, merokok, penggunaan anestesi lokal dengan vasokonstriktor, dan posisi gigi molar ketiga yang mengalami impaksi. Risiko terjadinya dry socket pada perokok lebih besar dibandingkan bukan perokok. Penelitian ini bertujuan untuk mengetahui kejadian dry socket pada perokok pasca tindakan odontektomi. Jenis penelitian berupa literature review menggunakan database Google Scholar, PubMed, dan Clinical Key. Hasil penelitian mendapatkan 10 artikel yang relevan dengan topik bahasan. Â Kejadian dry socket lebih sering terjadi pada perokok dibandingkan non perokok. Tingginya kejadian dry socket pada perokok dipengaruhi oleh kandung-an rokok antara lain, nikotin, karbon monoksida, dan hidrogen sianida. Nikotin berpengaruh terha-dap penurunan laju epitelisasi dan aliran darah, karbon monoksida menyebabkan penurunan kadar oksigen, dan hidorgen sianida dapat merusak metabolisme respirasi seluler. Bahan-bahan ini berkaitan dengan fase penyembuhan luka pada tahap inflamasi dan epitelisasi fibroplasia. Simpulan penelitian ini ialah kejadian dry socket pasca tindakan odontektomi lebih tinggi pada perokok dibandingkan non perokokKata kunci: dry socket; merokok; odontektomi